Pemrograman Multimedia Menggunakan Macromedia Flash - Marpaung, Adetya Maharani; Ritonga, Reni Septiani; Pane, Ogie Ariansah; Melsya, Laura; Ikhwan, Ali (Jurnal Sains dan Teknologi (JSIT), 2023)
Multimedia is the use of computers to present and combine text, sound, images, animation, audio, and video with tools and links to enable users to navigate, interact, create, and communicate. Programming and multimedia are a combination that connects how we design a program. which will be in the form of a multimedia. Macromedia Flash 8 is a very important plug-in in making animations and others. According to Akhmad in 2014, the Macromedia Flash application is a software plugin whose benefits are for opening or viewing animated images, videos as well as games that are on one of the website system plugins.